Incidence of Pelvic and Paraaortic Lymph Node Metastasis in Epithelial Ovarian Cancer at a Tertiary Care Center - Andrijono Andrijono; Risa Risfiandi (Indonesian Socety of Obstetrics and Gynecology, 2018)
Objective: To investigate the incidence of pelvic and paraaorticlymph node metastasis in epithelial ovarian cancer.Methods: This was a cross-sectional study. Data were collectedfrom medical records, and from the cancer registry 1539 medicalrecords were obtained. From there, 863 patients were operatedand 676 were not, and only 401 medical records were foundcomplete, and 306 samples were excluded because they have beentreated with NAC and underwent surgery, patients who underwentsurgery but the results is not the epithelium, and patients whounderwent surgery, but the results were benign or borderline. And95 patients who underwent primary surgery and lymphadenectomyonly 55 patients have results in lymphadenectomy. This study usesa calculation of sample size with categorial descriptions, withprecision of 3% then obtained a minimum sample size of 261patients.Results: According to the characteristics of the study subjectsabove, the results were stage I, II, III respectively 60%, 10.9%, and29%. The metastasized of the lymph node paraaortic 9.1%, andpelvic/paraaortic 20% pelvic/paraaortic23.6%. Based on thedegree of differentiation the results were good differentiation30.9%, moderate differentiation 23.6%, and poor differentiation45.5%. We found that paraaortic lymph node metastasis weremost frequent at stadium III (43.8%). In relationship betweenlymph node metastasis with differentiation of epithelial ovariancancer, the most frequent epithelial ovarian cancer were one withpoor differentiation in pelvic/paraaortic lymph node with the sumof 69.2%. From analysis, there is significant difference betweenserous hystologic subtype with mucinosum subtype in pelviclymph node, significant difference between serous hystologicsubtype and clear cell in paraorta or pelvic lymph node andbetween the serous histology subtype and mucinous as well.Conclusion: Lymph node metastasis incident of ovarian epithelialcancer in paraaorta amounts 20%, pelvic 9.1% and pelvic orparaaortic 23.6%. Higher the stadium, the lymph node involvementswill be higher as well (pelvic and paraaortic). In stadium 1of mucinous subtype with well differentiation has minimal lymphnode involvement so we can be more selective in considering therisk and benefit of lymphadenectomy.[Indones J Obstet Gynecol 2018; 6-1: 60-63]Keywords: lymph node metastasis, ovarian cancer